Are silver products an effective treatment for infection of chronic wounds? - Beck, Sarah (2014)
Abstract Aim; To identify whether silver is an effective treatment for infected chronic wounds and to identify any adverse effects. Background; Conflicting evidence exists around the effectiveness and adverse effects of silver products which has led to considerable confusion regarding this treatment in practice. With some previous systematic reviews and RCTs identifying that not enough evidence exists to recommend the use of silver products. However, a systematic review conducted by Lo et al (2008) identified that silver was an effective product for wound healing and reduction of infection levels, therefore it was important to identify if any RCTs had been published from this date to add weight to these conclusions. Methods; A systematic review of the literature was conducted using two search strategies in order to capture both effectiveness data (RCTs), and adverse effect data (RCTs & observational studies). For effectiveness searched; databases were searched from 2008- January 2014 using Cochrane CENTRAL, MEDLINE and EMBASE- including only randomised controlled trials. Adverse effects data was extracted from from the effectiveness results, with the additional searches performed to capture observational studies. This search was conducted from 1950- January 2014 using MEDLINE, EMBASE and CINAHL databases. Results; In total 5 RCTs and 4 observational studies were identified for inclusion in the review. It was identified that silver products are an effective treatment for infected chronic wounds, based on statistically significant results regarding wound healing and infection levels in the included controlled studies- and in combination with the results from the systematic review conducted by Lo et al (2008). Additionally, no serious adverse effects were identified. Conclusion; This systematic review strengthens the case for the use of silver products on managing locally infected chronic wounds. However, the use of silver must be accompanied by a thorough wound assessment; a “two week challenge” is recommended before reassessing for alternative treatment options.